“Prestación de servicio y su incidencia en el cumplimiento de las expectativas de los usuarios de la Cooperativa Interprovincial Macuchi del Cantón La Maná”. - Rodriguez Solano, Angie Mickaela (2022)
The research work investigates the provision of services and the fulfillment of the expectations of the users of the Cooperative Interprovincial Macuchi of the Canton La Maná, which presented a problem related to the incidence between the two variables. Therefore, the general objective is to analyze the provision of service and its impact on the fulfillment of expectations for improvement of the attention to the users of the Cooperative. The methodology used in the development of the research presents a descriptive level of type Bibliographic and field, analytical, deductive, quantitative and theoretical methods were also used, as well as the application of surveys aimed at partners and users of the Cooperative. Among the results obtained, both users (87%) and partners (56%) presented a tendency towards responses of the positive items which denotes strength of the instruction in the two variables by means of which it was possible to establish that users are satisfied with the service provided. The application of Spearman Spearman's Rho statistical method measured the relationship the relationship of each variable where it was shown that the relationship between the two variables is minimal so we proceeded to apply the statistical method Chi-Square where the dependence of each dimension was analyzed and it was determined that there is no non-dependence between the dimensions. Through the research carried out, it is concluded that the provision of service does not affect the fulfillment of expectations of the users of the Cooperative.